Contracts, Seagrass, and Discourses: nonhuman mediators in the planning of the Mangles Bay Marina. Issue 1 (2nd January 2020) - Quinn, Ryan
ABSTRACT: Planning with things other-than-human and exploring the more-than-human dimensions of cities has failed to ignite within the discipline of planning. Humans and the human perspective remain privileged throughout both planning theory and practice. However, slowly over the course of the past two decades there has been a trickle of Actor Network Theory-based planning studies allowing the discipline to dip its toes into the more-than-human realm. This paper uses empirical evidence to demonstrate the role and influence of particular nonhumans as active mediators in the politics of planning processes and the production of more-than-human urban spaces. In doing so, the paper raises ethical questions around the existing anthropocentric approach to the assessment and deliberation of planned development where living nonhumans are affected. Utilising the case study of the proposed Mangles Bay Marina, in the southern suburbs of Perth, Western Australia, the paper will illustrate the influence of three types of nonhuman actors: living nonhuman species; discursive text and talk; and technical artefacts.